Piecing earth & sky together : a creation story from the Mien tribe of Laos - Day, Nancy Raines; Panzarella, Genna ([Fremont, California] : Shen's Books, 2001)
While she and her grandmother work on their embroidery, Mei Yoon listens to an old Mein tale about the creation of the earth and the sky.
Keywords: Creation -- Folklore; Folk tales